Beispiel Nr: 07
$c=\log_{b} a \Leftrightarrow b^{c}=a \quad \log_c a+\log_c b = \log_c (a \cdot b) \quad \log_c a-\log_c b =\log _c\frac{a}{b} \quad log_c a^n=n\log_c a \\ \\ \textbf{Gegeben:} \\ {a=3 \qquad b=4 \qquad c=5 \qquad n=6}\\ \\ \textbf{Rechnung:} \\ \log_{4} 3 =0,792 \Leftrightarrow 4^{0,792}=3 \\ \log_{5} 3+\log_{5}4 = \log_{5}(3 \cdot 4)= \log_{5}(3 \cdot 4)=1,54 \\ \log_{5} 3-\log_{5}4 =\log_{5}\frac{3}{4}= -0,179\\ \log_{5}3^6=6\log_{5}3 = 4,1\\ \log_{4} 3=\dfrac{\log_{5}3}{\log_{5}4}=0,792 $